Artificial miniaturized luminescent materials based on perylene-covered glass surfaces12. (9th June 2017) - Mameri, Samir; Siekierzycka, Joanna R.; Brouwer, Albert M.
Abstract : Cu(i )-Catalyzed 1, 3-dipolar cycloaddition was used to construct a luminescent monolayer for an ICT-showing pyrrolidino-perylene association (5PMI) on glass surfaces, which represents a rare perylene chromophore, to date, anchored to a solid surface. Abstract : The reaction of perylene-monoimide3, upon Buchwald-type cross-coupling using a PEPPSI™-Ipr catalyst under anaerobic conditions, led to a novel dissymmetrical fluorophore4 . Compound1 displays a propargyl-terminated group which can be anchored to azido-functionalized glass surfaces, thus leading to a new class of miniaturized luminescent materials.